Revision of the Italian material of Juncus sect. Tenageia in the Herbarium Centrale Italicum: confirmations and novelties for Italy - Lastrucci, Lorenzo; Gambirasio, Valeria; Lazzaro, Lorenzo; Viciani, Daniele (Mediterranean Botany, 2022)
In this study, we carry out a revision of the Italian specimens belonging to Juncus L. subgenus Agathryon Raf. sect. Tenageia Dumort stored in the Herbarium Centrale Italicum of the Museum of Natural History of the University of Florence. By re-examining the 650 specimens present, we find that all the taxa belonging to this section are present in the herbarium. This work also allows us to highlight several novelties concerning species distribution at the regional level, thus confirming the importance of studying herbarium material. On the other hand, the work calls attention to a lack of information at the regional level for some taxa (e.g., J. sphaerocarpus), showing it would be desirable for botanists to continue to send samples to the herbarium to fill these gaps. This study also has implications for some museological issues, allowing the movement of specimens stored under ancient or obsolete names to the correct folders and to update the nomenclatural herbarium database, so contributing to the improvement of the future usefulness of these collections.